Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Kinerja Karyawan pada Sebuah Perusahaan Automotif di Tangerang Selatan - Wardani, Surti; Madina, Madina (Patria Artha University, 2023)
Intense competition in various automotive businesses requires proper HR management that support employee performance. One of the automotive companies is located in the South Tangerang area. The main objective of this research was to determine the effect of the work environment and work stress on employee performance at an automotive company in South Tangerang. The method used is quantitative research in causal associative approach. The sampling technique used was saturated sampling with 65 respondents. Data analysis techniques using descriptive, quantitative data analysis and also using the SPSS Version 26 application. The results obtained from data processing stated that all of the instrument tests were declared valid because the value of r hitung rtable, and also declared reliable because the CronbachAlpha value Standard Cronbach Alpha. In the classical assumption test, it states that the dependent variable and the independent variable are declared normally distributed because the significance value is 0.050, there is no multicollinearity obtained from the tolerance value of the variable 1 while the VIF value 10,this regression model has no autocorrelation which is indicated by a value of 1.948, and there is no heteroscedasticity disorder because the dots do not form a pattern. Quantitative analysis states that linear regression analysis X1 has a significant effect on Y, X2 has a significant effect on Y, while X1 and X2 simultaneously have a significant effect on Y. While X1 and X2 have a significanteffect on Y by 42.3%. Hypothesis test obtained value of F hitung F tabel or (42.345 2.750). This means that there is a simultaneous significant effect of work environment and work stress on employee performance at the automotive company in South Tangerang.